Revisiting the Concept of Dollarization : The Global Financial Crisis and Dollarization in Low-Income Countries - Mwase, Nkunde (IMF Working Papers; Working Paper ;, 2015)
The economic literature has examined deposit dollarization in nominal terms, typically focusing on the ratio of foreign currency deposits to broad money. However, while private agent demand for foreign currency may remain unchanged in foreign currency terms, there could be large fluctuations in the dollarization ratio simply due to exchange rate movements. This paper proposes a new approach to measuring dollarization that removes these exchange rate effects, and demonstrates that beyond the variance of inflation and depreciation, the level of inflation and size of depreciation also matter for dollarization. While dollarization in nominal terms surged during the recent global financial crisis, there was a downward trend in real terms. Employing a set of econometric estimators, this paper investigates whether 'real' dollarization during 2006-09 was associated with the crisis, and the role of initial macroeconomic conditions, quality of institutions, risk aversion, and prudential measures. We find that exchange rate appreciation and reductions in sovereign risk do moderate dollarization; but the results for global volatility have low statistical significance, perhaps because global shocks tend to preserve, to a large extent, relative attractiveness of foreign assets. Nonetheless, estimated impulse-response functions point to a large but short-lived positive impact of global volatility on dollarization, which could reflect economic agents heightened concerns about spillover effects of global uncertainty on the domestic economy.